Diagnosis of immunomarkers in vivo via multiplexed surface enhanced Raman spectroscopy with gold nanostars. Issue 27 (2nd July 2018) - Ou, Yu-Chuan; Webb, Joseph A.; O'Brien, Christine M.; Pence, Isaac J.; Lin, Eugene C.; Paul, Eden P.; Cole, Danielle; Ou, Shih-Hao; Lapierre-Landry, Maryse; DeLapp, Rossane C.; Lippmann, Ethan S.; Mahadevan-Jansen, Anita; et al.
Abstract : In this work biomarkers PD-L1 and EGFR are diagnosed in mouse tumors in vivo and ex vivo with surface-enhanced Raman spectroscopy. Abstract : In this work, we demonstrate the targeted diagnosis of immunomarker programmed death ligand 1 (PD-L1) and simultaneous detection of epidermal growth factor receptor (EGFR) in breast cancer tumors in vivo using gold nanostars (AuNS) with multiplexed surface enhanced Raman spectroscopy (SERS). Real-time longitudinal tracking with SERS demonstrated maximum accumulation of AuNS occurred 6 h post intravenous (IV) delivery, enabling detection of both biomarkers simultaneously. Raman signal correlating to both PD-L1 and EGFR decreased by ∼30% in control tumors where receptors were pre-blocked prior to AuNS delivery, indicating both the sensitivity and specificity of SERS in distinguishing tumors with different levels of PD-L1 and EGFR expression. Our in vivo study was combined with the first demonstration of ex vivo SERS spatial maps of whole tumor lesions that provided both a qualitative and quantitative assessment of biomarker status with near cellular-level resolution. High resolution SERS maps also provided an overview of AuNS distribution in tumors which correlated well with the vascular density. Mass spectrometry showed AuNS accumulation in tumor and liver, and clearance via spleen, and electron microscopy revealed AuNS were endocytosed in tumors, Kupffer cells in the liver, and macrophages in the spleen. This study demonstrates that SERS-based diagnosis mediated by AuNS provides an accurate measure of multiple biomarkers both in vivo and ex vivo, which will ultimately enable a clinically-translatable platform for patient-tailored immunotherapies and combination treatments.